State-controlled entities control nearly US 2 trillion in foreign assets - Karl P. Sauvant; Jonathan Strauss (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
State-controlled entities (SCEs) – especially state-owned enterprises (SOEs) – are important players in the world FDI market. Among the 100 largest MNEs from developed countries and the 100 largest from emerging markets, at least 49 are SOEs. They control nearly US 2 trillion in foreign assets, the bulk of them by MNEs headquartered in developed countries. Care needs to be exercised that regulatory initiatives regarding SCEs do not lead to a fragmentation of the international investment law regime.
Keywords: 330